Learning Independence and Learning Motivation as Determinants of Increasing Students’ Critical Thinking Ability in 21st Century Learning - Ginting, Dafid; Sinaulan, Jeffry H.; Ginting, Nurlelasari; Warwer, Fredrik; Affandi, Lukman; Siagian, Ade Onny (Edumaspul: Jurnal Pendidikan, 2023)
This research is motivated by the importance of critical thinking skills. The purpose of this study was to examine and analyze learning independence and learning motivation as determinants of increasing students’ critical thinking in 21st century learning. This study used a quantitative approach with a survey method. The sampling technique used purposive sampling of 100 students. The instruments used are tests and questionnaires. The data analysis technique used is the classical assumption, correlation analysis, and multiple linear regression analysis including hypothesis testing T test, F test and R2 test. 1) Learning independence has a positive and significant effect on students’ critical thinking skills in 21st century learning, 2) Learning motivation has a positive and significant effect on students’ critical thinking skills in 21st century learning, and 3) Learning independence and learning motivation have a positive effect and significant effect on students’ critical thinking skills in 21st century learning. The findings of this study indicate the importance of independent learning and learning motivation in improving students’ critical thinking skills.